Examining the Prevalence of Congenital Anomalies in Newborns: A Cross-Sectional Study at a Tertiary Care Maternity Hospital in Saudi Arabia - Bayapa Reddy Narapureddy; Yousef Zahrani; Hind Eissa Musa Alqahtani; Bharat Kumar Mamilla Mugaiahgari; Lingala Kalyan Viswanath Reddy; Shaik Mohammed Asif; Mohammad Ali Abdullah Almoyad; Ali Mohieldin; Adam Dawria (MDPI AG, 2024)
Background: Congenital anomalies, representing structural or functional abnormalities present at birth, pose a substantial global health challenge, affecting 8 million newborns annually. With 3.3 million succumbing before age five and 3.2 million facing physical or mental disability, their diverse causes necessitate comprehensive understanding for effective healthcare planning. This study explores the prevalence of congenital anomalies among newborns in the Abha Maternity and Children Hospital (MCH) in Abha, Kingdom of Saudi Arabia. Methodology: A descriptive cross-sectional record-based study was conducted on newborns born between 2018 and 2022. Data were gathered in 4 months from September to December 2023. Purposive sampling was employed to select the case records of newborns with congenital anomalies after careful screening and considering inclusion and exclusion criteria. Data was acquired through a self-designed study tool, and the data were entered into Google Forms. Results: Congenital anomalies' five-year prevalence was 3.21%, and one year, in 2022, the prevalence was 4.02%. Female neonates exhibited higher anomalies (59.3%), and preterm births accounted for 39.6%, emphasizing their vulnerability. The findings indicate that consanguineous marriages are linked to 63.3% of anomalies, notably neural tube defects (25%) and congenital heart diseases (19.7%). Anomalies are not significantly associated with consanguinity or birth order, but maternal age, education, employment, and antenatal maternal medical issues are associated considerably. Conclusions: These study insights contribute to health planners planning targeted interventions and awareness programs that are crucial to mitigate risks associated with preterm births and consanguineous marriages. The promotion of 100% antenatal screening and prophylactic medication for high-risk women and couples is necessary to prevent inherited deformities. In future the Ministry of Health must plan large-group prospective research to better understand the associated risk factors that will help public health initiatives minimize congenital-associated neonatal mortality and improve pregnancy outcomes.